F-actin-binding protein drebrin regulates CXCR4 recruitment to the immune synapse - Pérez-Martínez, Manuel; Gordón-Alonso, Mónica; Cabrero, José Román; Barrero-Villar, Marta; Rey, Mercedes; Mittelbrunn, María; Lamana, Amalia; Morlino, Giulia; Calabia, Carmen; Yamazaki, Hiroyuki; Shirao, Tomoaki; Vázquez, Jesús; et al. (Journal of cell science, 2010)
The adaptive immune response depends on the interaction of T cells and antigen-presenting cells at the immune synapse. Formation of the immune synapse and the subsequent T-cell activation are highly dependent on the actin cytoskeleton. In this work, we describe that T cells express drebrin, a neuronal actin-binding protein. Drebrin colocalizes with the chemokine receptor CXCR4 and F-actin at the peripheral supramolecular activation cluster in the immune synapse. Drebrin interacts with the cytoplasmic tail of CXCR4 and both proteins redistribute to the immune synapse with similar kinetics. Drebrin knockdown in T cells impairs the redistribution of CXCR4 and inhibits actin polymerization at the immune synapse as well as IL-2 production. Our data indicate that drebrin exerts an unexpected and relevant functional role in T cells during the generation of the immune response.